2023
DOI: 10.3847/1538-4357/acb2c8
|View full text |Cite
|
Sign up to set email alerts
|

An 8.0% Determination of the Baryon Fraction in the Intergalactic Medium from Localized Fast Radio Bursts

Abstract: The dispersion measure (DM)–redshift relation of fast radio bursts (FRBs) has been proposed as a potential new tool for probing the intergalactic medium (IGM) and for studying cosmology. However, poor knowledge of the baryon fraction in the IGM (f IGM) and its degeneracy with cosmological parameters impose restrictions on the cosmological applications of FRBs. Furthermore, DMs contributed by the IGM (DMIGM) and host galaxy (DMhost), important cosmological quantities, cannot be exactly extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…For the SN sample, we use the 1048 Pantheon SNe Ia [48]. Please see [56] for more details on the exact compilations and the likelihood functions of these cosmological probes. The final log-likelihood is thus a sum of the separated likelihoods of FRBs, CMB, BAO, and SNe Ia:…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the SN sample, we use the 1048 Pantheon SNe Ia [48]. Please see [56] for more details on the exact compilations and the likelihood functions of these cosmological probes. The final log-likelihood is thus a sum of the separated likelihoods of FRBs, CMB, BAO, and SNe Ia:…”
Section: Data and Resultsmentioning
confidence: 99%
“…Although some numerical simulations and observations suggested that f IGM is slowly evolving with redshift [53][54][55], a recent study indicated that such evidence is absent in the relatively small amount of FRB data [56]. Here we thus consider f IGM as a constant.…”
Section: Jcap09(2023)025mentioning
confidence: 96%
“…Subsequently, the resultant membrane was sequentially immersed in H 2 O 2 solution and H 2 SO 4 for 1 h. Ultimately, following an extensive rinsing process with deionized water, the iHOF/Nafion composite membranes were successfully obtained. Similarly, CS/HOF membrane, 34 CS/PVA/LPB/2D-HOF Composite Membrane, 42 iHOF-9/Nafion membrane, 47 and HOF-21@Pebax membrane 48 have also been prepared using this method.…”
Section: Fabrication Of Hof-based Membranesmentioning
confidence: 99%
“…The imperative technology for energy-efficient and environmentally sustainable CO 2 separation is also growing rapidly, owing to its significant market potential within a range of industrial applications, including CO 2 capture, the separation of CO 2 from flue gas (CO 2 /N 2 ), the purification of natural gas (CO 2 /CH 4 ), as well as the purification of H 2 (CO 2 /H 2 ). As a typical example, Wang et al 48 exhibited the use of a HOF-based mixed-matrix membrane for CO 2 separation. The blended HOF-21 nanoparticles imparted the mixed-matrix membrane with additional mass transfer channels and chemical functionality.…”
Section: Applications Of Hof-based Membranesmentioning
confidence: 99%
“…The DM is the integral over the number density of free electrons along the propagation path between the source and observer, which contains important information on the cosmological distance. Therefore, the combined DM and redshift information of FRBs can be used to study cosmology, such as constraining the baryon number density of the Universe (Deng & Zhang 2014;McQuinn 2014;Macquart et al 2020;Yang et al 2022), the dark energy equation of state (Gao et al 2014;Zhou et al 2014;Walters et al 2018;Wei et al 2018;Zhang & Li 2020;Zhao et al 2020;Qiu et al 2022), cosmic reionization history (Deng & Zhang 2014;Zheng et al 2014;Hashimoto et al 2021), cosmic proper distance (Yu & Wang 2017), the baryon mass fraction in the intergalactic medium (IGM; Li et al 2019Li et al , 2020Walters et al 2019;Wei et al 2019;Wang & Wei 2023), the Hubble constant (Hagstotz et al 2022;James et al 2022b;Wu et al 2022), and so on. Additionally, strongly lensed FRBs have also been proposed for probing the nature of compact dark matter (Muñoz et al 2016;, for measuring the Hubble constant and cosmic curvature (Li et al 2018), and for determining the post-Newtonian parameter (Abadi & Kovetz 2021;Gao et al 2022).…”
Section: Introductionmentioning
confidence: 99%